Bamboo - Current and Future Prospects 2018
DOI: 10.5772/intechopen.76475
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancement in Physico-Mechanical and Thermal Studies of Bamboo and Its Fibers

Abstract: Bamboo has its own role in the development of society. It is widely used as a support tools for sustainable farming and being exceptional resource for variety of income and employment-generating systems. This overlooked biomass provides food, raw material, shelter, medicine for large part of world's population. Bamboo has given a great support to mankind by providing building materials that are extensively used for household products. It has found a good place for industrial applications due to advances in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Bamboo can be harvested in 3-5 years [1]. The advantages of bamboo fiber are low cost, high availability, and the specific strength is comparable with glass fiber [2][3][4][5]. However, one of the disadvantages of natural fiber composites is the high variability in strength and highwater absorption [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo can be harvested in 3-5 years [1]. The advantages of bamboo fiber are low cost, high availability, and the specific strength is comparable with glass fiber [2][3][4][5]. However, one of the disadvantages of natural fiber composites is the high variability in strength and highwater absorption [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo material is mainly composed of cellulose, hemicelluloses, lignin, and aqueous extracts. Research on the thermal decomposition of the chemical components of bamboo demonstrated that at high temperatures, the decomposition of hemicelluloses begins first, followed by cellulose, and finally lignin 23,24 . Liu et al have investigated the combustion characteristics of bamboo materials and found that in the temperature range of 200°C to 300°C, the degradation is related to the decomposition of hemicelluloses and cellulose 12 .…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive thermo-chemical characterisation should be conducted to understand the degradation of the different compounds of bamboo, since the fibre bundles and the parenchyma tissue have different effects on the load-bearing capacity of bamboo. Whereas the fibres are mainly responsible for the tensile strength, the parenchyma plays a fundamental role in supporting the fibre bundles under compression, besides giving the strength of bamboo under shear stress parallel to the fibres (Rizal et al 2018).…”
Section: Thermal Degradation Of Bamboomentioning
confidence: 99%